Experimental animal models of pulmonary hypertension: Development and challenges - Xiao‐Han Wu; Jie‐Ling Ma; Dong Ding; Yue‐Jiao Ma; Yun‐Peng Wei; Zhi‐Cheng Jing (Animal Models and Experimental Medicine, 2022)
Abstract Pulmonary hypertension (PH) is clinically divided into 5 major types, characterized by elevation in pulmonary arterial pressure (PAP) and pulmonary vascular resistance (PVR), finally leading to right heart failure and death. The pathogenesis of this arteriopathy remains unclear, leaving it impossible to target pulmonary vascular remodeling and reverse the deterioration of right ventricular (RV) function. Different animal models have been designed to reflect the complex mechanistic origins and pathology of PH, roughly divided into 4 categories according to the modeling methods: non‐invasive models in vivo, invasive models in vivo, gene editing models, and multi‐means joint modeling. Though each model shares some molecular and pathological changes with different classes of human PH, in most cases the molecular etiology of human PH is poorly known. The appropriate use of classic and novel PH animal models is essential for the hunt of molecular targets to reverse severe phenotypes.